Psychological burnout and its relationship to job satisfaction for nurses in the government health sector in Riyadh - Al-Mutairi, Nouf Khalifa; Al-Mutairi, Mona Khalifa; Al-Mutairi, AlHanouf Khalifa (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the nature of the relationship between psychological burnout and job satisfaction for nurses in the government health sector in Riyadh, as well as to identify the level of psychological burnout and the level of job satisfaction among nurses working in the government health sector in Riyadh. The researchers used the descriptive analytical method to identify the objectives of the study, and the study population included all nurses in the governmental health sector in Riyadh. The study sample consisted of (410) nurses in the government health sector in Riyadh, who were chosen randomly. The researchers used two tools to achieve the objectives of the study and all its data are: the burnout scale and the job satisfaction scale. In light of this, the study reached a number of results, the most important of which is the existence of an inverse (negative) relationship with statistical significance between the total degree of psychological burnout and the total degree of job satisfaction. In light of the results, the study recommends the need to prepare counseling programs to reduce the feeling of psychological burnout and increase job satisfaction, and the need to pay attention to preventive income in order to achieve professional and psychological compatibility among nurses in the Saudi health sector. and the necessity of training nurses with specialized professional courses to provide the necessary instructions in order to train them on methods of dealing, adapting to and confronting stressful situations.